Low-magnitude high-frequency vibration attenuates sarcopenia by modulating mitochondrial quality control via inhibiting miR-378 - Long, Yu-Feng; Cui, Can; Wang, Qianjin; Xu, Zhen; Chow, Simon Kwoon-Ho; Zhang, Ning; Wong, Ronald Man Yeung; Chui, Elvis Chun-Sing; Schönmehl, Rebecca; Brochhausen, Christoph; Rubin, Clinton; Li, Gang; et al. (Journal of cachexia, sarcopenia and muscle, 2025)
Background Sarcopenia, the age-related decline in muscle mass and muscle strength, significantly contributes to falls, diminished quality of life, and mortality. Although mitochondrial dysfunction is increasingly implicated in sarcopenia, the underlying mechanisms are not fully discovered. Low-magnitude high-frequency vibration (LMHFV), a recommended treatment by the Centers for Disease Control and Prevention (CDC) to reduce fall risk, remains poorly understood of the mechanism on improving skeletal muscle quality. This study aims to investigate whether mitochondrial dysfunction contributes to sarcopenia and evaluate whether LMHFV mitigates sarcopenia by improving mitochondrial homeostasis. Methods The relationship between mitochondria dysfunction and sarcopenia using senescence accelerated mice prone 8 (SAMP8) model was investigated, assessing muscle and mitochondria. The effects of LMHFV on muscle and mitochondria were evaluated in SAMP8 mice during sarcopenia progression. The role of miR-378 in muscle and mitochondrial homeostasis were evaluated in SAMP8 mice and transgenic over-expressing miR-378 mice (TG mice). The target gene of miR-378 was investigated by dual-luciferase reporter assay in C2C12 cells. Subsequently, we evaluated the effect of LMHFV on miR-378 using both mouse models. Results Reduction in muscle strength was observed from the ages of month 8 to 10 in SAMP8 mice (grip strength decreased 27.1%, p = 0.0263; twitch force decreased 29.1%, p = 0.0178; tetanic force decreased 29.9%, p = 0.011), as well as muscle atrophy (cross-section area: 38.3%, p = 0.0121). Mitochondrial morphological deterioration was noticed from month 6 to 10. Mitochondrial homeostasis, including biogenesis, fusion, fission, mitophagy, and ATP production declined from month 6 to 10. Compared to control group at month 10, knocking down miR-378 in SAMP8 mice mitigated sarcopenia (twitch force increased 44.3%, p = 0.0023; tetanic force increased 51.9%, p = 0.0005), improved mitochondrial morphologies (mitochondrial number increased 1.65-fold, p = 0.0023; mitochondrial density increased 1.65-fold, p = 0.0023; mitochondrial relative area increased 9.05-fold, p = 0.0019) along with improved mitochondrial homeostasis. Over-expressing miR-378 in transgenic mice exacerbated muscle atrophy and mitochondrial deterioration significantly. The dual-luciferase reporter assay in C2C12 cells revealed that miR-378 inhibited PGC-1α directivity. LMHFV was found to mitigate sarcopenia by modulating mitochondrial homeostasis, such as attenuating mitochondrial morphological deterioration and improving mitochondrial biogenesis through increasing PGC-1α via inhibiting miR-378 in skeletal muscle. Conclusions Our findings indicate that mitochondrial biogenesis, fusion, fission, and mitophagy were compromised during progression of sarcopenia, with mitochondrial deterioration preceding the onset of sarcopenia symptoms. The study also demonstrated that LMHFV could attenuate sarcopenia by modulating mitochondrial quality control through inhibiting miR-378, highlighting its therapeutic potential in the management of age-related muscular degeneration.